Toward Mitho-pimatisowin: A Framework for FNMI Engagement Through Relationality - Molloy, Sean Anthony, Mr. (Scholarship@Western, 2023)
Abstract Indigenous Peoples have experienced harm from colonial beliefs and practices, and one does not need to look beyond the current systems of public education to see evidence of this. This Organizational Improvement Plan (OIP) provides a challenge to the conservative, neoliberal, and Eurocentric orthodoxy that is pervasive in one northern Saskatchewan context, and advocates for a need and a framework to reorient our learning community so that First Nation, Métis and Inuit (FNMI) students and partners see relevance and feel engaged with our organization, thereby producing more positive educational outcomes. With 80% of students identifying as FNMI, and the surrounding community reflecting this demographic, culturally relevant concepts are necessary to guide organizational change. Relationality has been identified as essential for many FNMI peoples, so the local Cree concept of mitho-pimatisowin, meaning one’s necessity to acknowledge and respect all relations and to accept responsibility for them (Cardinal & Hildebrandt, 2020; Settee, 2011), is a key concept to direct and measure the existing organizational climate and change initiatives, and to prioritize the creation and maintenance of strong relationships between all partners who serve our students and the surrounding community. In support of mitho-pimatisowin, an emphasis on team and inclusive leadership will operate through a social constructivist lens so that all our partners can begin to construct meaningful alliances and understandings within a critical paradigm. An emphasis on enhancing our organizational relationships will ensure a culture of collective efficacy is developed, and this will re-center Indigenous worldviews and epistemologies so that they work in collaboration with Western approaches, thereby improving relations and FNMI student engagement. Keywords: Mitho-pimatisowin, Indigenous, psychological safety, education, social constructivism, inclusive leadership, team leadership